Species of Cuscus in Taman Wisata Gunung Meja Manokwari Regency, West Irian Jaya - ANTON SILAS SINERY (Society for Indonesian Biodiversity, 2006)
One element of the biodiversity richness at Papua is its mammal especially marsupials. According to Petocz, (1987) there are 154 mammal species in Papua. One of them is cuscus. Menzies (1991) stated that 11 cuscus species exist in New Guinea, five species occur in Papua. Menzies (1991) also mentioned that the habitat, distribution and behavior of each species is not fully known yet and one strategy to answer the above mentioned questions is by conducting an explorative study of cuscus in several areas of Papua. This research to know species of cuscus in Taman Wisata Gunung Meja Manokwari using a descriptive method and observation technique. The result indicated that there was two species of cuscus in this area namely timor cuscus (Phalanger orientalis) and common spotted cuscus (Spilocuscus maculatus). There was 26 plant species feeding food of these cuscus species. © 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: feding, location, herons, mudflat, rice-field, grass-land, fisheries